Effect of friction stir welding on the tensile properties of AA6063 under different conditions - Singha R.; Rizvi S.A.; Tewari S.P. (My University, 2025)
The basic aim of present study is to examine the effect of main friction stir welding (FSW) parameters on the quality of AA 6063 plate welds. Welding of AA6063 was carried out by a vertical milling machine, using different tools with a stationary shoulder and during the welding no external heating system was used. Different welding parameters studied were the tool rotational speed which varied from 2700 to 5400 (rpm), the traverse speed of table which varied from 12 to 17 (mm/min), and the tool shoulder diameter ranging from 17 to 22 mm. In the present research three levels, three factorial designs were used for optimization by taguchi approach. The results indicated that tensile strength of welded joint was increasing with rotational speed and decreasing with increasing transverse feed because frictional heat was directly proportional to rotational speed of tool. © 2017, Materials and Energy Research Center. All rights reserved.